ʺTo the issue of importance to prepare vocational teachers for research activitiesʺ - Bachiieva, L. (Problems of Engineer-Pedagogical Education, 2024)
Ensuring the quality of vocational teacher training is currently one of the most urgent tasks. They are the ones who are tasked to satisfy industries with qualified specialists despite the challenges facing the educational system in general and the unique conditions faced by each individual educational institution, teacher, and student. One of the ways to solve this problem is to train teachers to design methodological systems based on the results of research on industry and educational trends. Our study aims to contribute to the discussion on the relevance of training vocational teachers to study the innovative trends of Industry 4.0 and Industry 5.0 to formulate relevant goals and content of methodological systems; characteristics of Education 4.0 for the development of educational methods, forms, and means; formulation of requirements for the student's qualities and components of the teacher's professional competence according to the generalized impact of these provisions. At the methodological level, the study is mainly based on a review of regulatory sources and scientific publications. The first section presents an analysis of legislative and regulatory documents, identifies the key tasks for the development of scientific and research activities in national education. It has been determined that a teacher can create and implement author's methodological systems to solve educational problems in theory and practice. The second section focuses on the analysis of Industry 4.0 and Industry 5.0 trends and their impact on the goals and content of educational information. The third section is devoted to the analysis of Education 4.0 trends, and it has been determined that they guide the teacher in choosing educational methods, forms and means of teaching. Examples of research questions that can be considered by vocational teachers when designing methodological systems are formulated. The conclusions reflect scientific generalizations about the relevance of training vocational teachers for research activities to design methodological systems